Cost‐Effectiveness of Clopidogrel‐Aspirin Versus Aspirin Alone for Acute Transient Ischemic Attack and Minor Stroke. Issue 3 (5th June 2014) - Pan, Yuesong; Wang, Anxin; Liu, Gaifen; Zhao, Xingquan; Meng, Xia; Zhao, Kun; Liu, Liping; Wang, Chunxue; Johnston, S. Claiborne; Wang, Yilong; Wang, Yongjun; ,
Abstract : Background: Treatment with the combination of clopidogrel and aspirin taken soon after a transient ischemic attack (TIA) or minor stroke was shown to reduce the 90‐day risk of stroke in a large trial in China, but the cost‐effectiveness is unknown. This study sought to estimate the cost‐effectiveness of the clopidogrel‐aspirin regimen for acute TIA or minor stroke. Methods and Results: A Markov model was created to determine the cost‐effectiveness of treatment of acute TIA or minor stroke patients with clopidogrel‐aspirin compared with aspirin alone. Inputs for the model were obtained from clinical trial data, claims databases, and the published literature. The main outcome measure was cost per quality‐adjusted life‐years (QALYs) gained. One‐way and multivariable probabilistic sensitivity analyses were performed to test the robustness of the findings. Compared with aspirin alone, clopidogrel‐aspirin resulted in a lifetime gain of 0.037 QALYs at an additional cost of CNY 1250 (US 192), yielding an incremental cost‐effectiveness ratio of CNY 33 800 (US 5200) per QALY gained. Probabilistic sensitivity analysis showed that clopidogrel‐aspirin therapy was more cost‐effective in 95.7% of the simulations at a willingness‐to‐pay threshold recommended by the World Health Organization of CNY 105 000 (US 16 200) per QALY. Conclusions: Early 90‐day clopidogrel‐aspirin regimen for acute TIA or minor stroke is highly cost‐effective in China. Although clopidogrel is generic, Plavix is brand in China. If Plavix were generic, treatment with clopidogrel‐aspirin would have been cost saving.